One‐Pot Preparation of Dimethyl Isosorbide from d‐Sorbitol via Dimethyl Carbonate Chemistry. Issue 1 (22nd December 2016) - Aricò, F.; Aldoshin, A. S.; Tundo, P.
Abstract: Direct synthesis of dimethyl isosorbide (DMI) fromd ‐sorbitol via dimethyl carbonate (DMC) chemistry is herein first reported. High yield of DMI was achieved using the nitrogen superbase 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) as catalyst and performing the reaction in a stainless steel autoclave by increasing the temperature from 90 to 200 °C. In this procedure, DMC features its full capacity acting in the different steps of the process as carboxymethylating, leaving‐group (cyclization), and methylating agent; DMC is also employed as the reaction media. Abstract : Multipurpose DMC : Dimethyl isosorbide (DMI) is synthesized for the first time via a one‐pot reaction starting from its parent alcohold ‐sorbitol via dimethyl carbonate (DMC) chemistry. DMC acts in the different steps of the process as carboxymethylating, leaving‐group (cyclization), and methylating agent as well as being the reaction media.